2016
DOI: 10.1002/dc.23430
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fine‐needle aspiration and ultrasound‐based characteristics of thyroid nodules for diagnosing malignancy in Iranian patients

Abstract: Among sonography findings, width and area of nodule, calcification, and nodule border have significant effect on malignancy diagnosis. Also FNA is necessary in nodules with calcification, border irregularity, and less width and area, especially in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Size plays a notable role in determining the need of ine needle aspiration (FNA) for a thyroid nodule; however, ultrasound features can provide valuable clues regarding malignancy of nodules [108]. These are hypoechogenicity, a solid internal structure, irregular margins, microcalciications, taller-than-wide shape, and evidence of extrathyroidal extension or cervical lymphadenopathy for papillary thyroid cancers.…”
Section: Assessment and Treatment Of Thyroid Nodulesmentioning
confidence: 99%
“…Size plays a notable role in determining the need of ine needle aspiration (FNA) for a thyroid nodule; however, ultrasound features can provide valuable clues regarding malignancy of nodules [108]. These are hypoechogenicity, a solid internal structure, irregular margins, microcalciications, taller-than-wide shape, and evidence of extrathyroidal extension or cervical lymphadenopathy for papillary thyroid cancers.…”
Section: Assessment and Treatment Of Thyroid Nodulesmentioning
confidence: 99%
“…In addition, the authors reported that some patients underwent central lymph node dissection (CLND) and others did not when the tumor was lesser than 5mm or cytology results were not determined; provided that cytology does not have a100% sensitivity and specificity. The results should be confirmed by pathology as the gold standard and be matched with ultrasound characteristics of nodules to see whether malignancy is present or not (2). So some cases may not be PTC patients which have impacts on the recurrence and survival rates in the present study.…”
Section: Can We Really Consider Tumor Size and Surgical Extent As Pre...mentioning
confidence: 81%
“…[18,19] Fine-needle aspiration biopsy has acceptable specificity and sensitivity for thyroid cancers. [17] With the usage of thyroid FNAB, the diagnosis of thyroid cancer has increased twice in the last five decades. Cibas and Ali [20] reported that the routine usage of thyroid FNAB leads to an increased rate of detection of cancer in thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21] Significant information was obtained in studies investigating the compliance of sonographic findings with thyroid FNAB. Akhawan et al [17] compared the correlation between thyroid sonography findings and FNAB results and reported that the nodule surface area was the most correlated sonographic finding with malignancy. Irregular nodule boundaries calcification and hypervascularity were the most prominent findings in malignancy in USG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation